Burgos, Juan Manuel, La vía de la experiencia o la salida del laberinto, Rialp, Madrid, 2018, 138 pp - Massini Correas, Carlos I. (2021)
Fil: Massini Correas, Carlos I. Universidad de Mendoza; Argentina